An epidemiological study regarding availability and utilization of public health care services in slum in Amritsar city - Verma, Richa; Singh, Tejbir; Lal, Mohan; Kaur, Jasleen; Mahajan, Sanjeev; Deepti, Shyam Sunder (International Journal Of Community Medicine And Public Health, 2019)
Background: Low level of education of the slum dwellers along-with poor socio- economic status and pathetic environmental conditions lead to their poor health indicators. Since the National Urban Health Mission (NUHM) was launched in 2013, the health services are still in their initial stages. Assessment of the availability as well as the utilization of health care services of the urban slums is the need of the hour. Methods: The cross-sectional study was conducted in randomly selected slum in Amritsar city. All the houses were enumerated and visited by the interviewer herself. The eldest adult member of the family was selected as key respondent and written, informed consent was obtained. Predesigned questionnaire was used to collect the data which was then compiled and analyzed using statistical tests. Results: Out of the total respondents, one third respondents had knowledge about the government health center nearby (statistically significant) while out of these, only one third utilized the services at the center (statistically non-significant). Almost half of the respondents had knowledge about the medical camps and out of these, two-thirds utilized the services at medical camps. Conclusions: Overall utilization of services is poor. More respondents were aware of the medical camps than the static government health facility and utilization of medical camps was also more. So the static health services under NUHM need to be further strengthened.